Search for the standard model Higgs boson in the H -> ZZ -> l(+)l(-)tau(+)tau(-) decay channel in pp collisions at root s=7 TeV - Chatrchyan, S; Khachatryan, V; Sirunyan, A; Tumasyan, A; Adam, W; Bergauer, T; Dragicevic, M; Eroe, J; Fabjan, C; Friedl, M; Fruehwirth, R; Ghete, V; et al. (2012)
A search is reported for the standard model Higgs boson in the H → ZZ → l +l -τ +τ - decay mode, where l = μ or e, in proton-proton collisions at □s = 7TeV, corresponding to an integrated luminosity of 4.7 fb-1 collected with the CMS detector at the LHC. No evidence is found for a significant deviation from the background expectation. An upper limit four to twelve times larger than the predicted value is set at 95% confidence level for the product of the standard model Higgs boson production cross section and decay branching fraction in the mass range 190 < mH < 600 GeV. © 2012 SISSA.